Pandangan Disabilitas dan Aksesibilitas Fasilitas Publik bagi Penyandang Disabilitas di Kota Malang - Thohari, Slamet (INDONESIAN JOURNAL OF DISABILITY STUDIES (IJDS), 2014)
The paper traces how people in Malang percieve people with disabilities, therefore it looks for the base-line of accessibility on public services for people with disabilities as well. Itâs nased on a reseach used a quantitaif method in which we use samples based on the standard regulated by goverment.Â  On the other hand, a survey on perception of people with disability in Malang, it used clustering method which is investigating disability issues to people in Malang based on area already pointed out. Our Finding shows that people in Malang beleived that people with disabilities are âunperfect peopleâ, therefe they still beleive on special schools. The other results showed that public services in Malang are not accessible for people with disabilities. The trend data showed that almost of public facilities are categorized as ânot accesibleâ, only some can be categorized as âless-accesibbleâ and 0% of public facilities are âaccessible.